Strategic Entrepreneurship in the Digital Economy: Opportunities and Challenges for SMEs - Hernaningsih, Fery (Baca Dulu Publisher, 2025)
This study aims to analyze how strategic entrepreneurship enables small and medium enterprises (SMEs) to leverage opportunities and overcome challenges in the digital economy. Using a quantitative research approach, data were collected from 250 SME owners and managers across digitally engaged sectors such as e-commerce, creative industries, and food and beverage businesses. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed to examine the relationships among digital opportunities, digital challenges, strategic entrepreneurship, and SME performance. The results reveal that digital opportunities have a significant positive influence on strategic entrepreneurship, while digital challenges exert a negative but manageable impact. Moreover, strategic entrepreneurship demonstrates a strong positive effect on SME performance, resilience, and sustainability, and mediates the relationship between digital economy factors and business outcomes. These results imply that SMEs can achieve superior performance and long-term competitiveness through strategic entrepreneurial behavior that aligns innovation, resource orchestration, and opportunity recognition within digital transformation efforts. The novelty of this study lies in integrating the dual role of opportunities and challenges in the digital economy with strategic entrepreneurship as a mediating mechanism that fosters sustainable growth among SMEs.